Assessment of Biological Spectrum and Phenological Behaviours of Coastal Vegetation in East Midnapore District, Eastern India - Sen, Uday Kumar; Bhakat, Ram Kumar (Journal of Tropical Life Science, 2020)
The open coastlines of the world are dominated by sand dunes and salt marshes. They are the primary areas for human recreation and provide a wide range of frequently overlooked ecosystem services. Their intrinsic ecological significance lies in having unique biological assemblies and supporting a range of ecological processes, such as water filtration and nutrient cycling. In addition, in the coastal zone, these areas link marine and terrestrial systems. The objective of this paper is to check the psammophytic species diversity, conservation status and threat; and also prepare a biological spectrum m in the Costal East Midnapore (CEM) district's sand dune and salt marsh areas. A part of floristic inventories in the CEM, various field trips in different season were carried out, quadrate method is done to examine the ecological impact and richness. Specimens were collected, prepared voucher specimen and enlisted according APG IV classification system to prepare biological spectrum. CEM vegetation was diverse and composed of 162 species of 132 genera distributed among 52 families of 28 orders according to APG IV classification, of which 37 species were exotics. Fabales (19.14%) and Fabaceae (19.14%) were the dominant order and family. Biological spectrum shows the study area was classified as â€œthero-chamaephyticâ€ type of phytoclimate. Mesophyll (24.07%) and lanceolate as well as oblong (19.14%) were found to be high in the leaf size spectrum and lamina. The area of study was highly ecotonal potential and fairly undisturbed. This study is useful in comparing and contrasting the adjacent natural vegetation along the gradients of the environment; and recommends effective long-term conservation and better management of the coastal area.